2020
DOI: 10.3390/biomedicines8100435
|View full text |Cite
|
Sign up to set email alerts
|

CRP Is Transported by Monocytes and Monocyte-Derived Exosomes in the Blood of Patients with Coronary Artery Disease

Abstract: The objective of this work was to study the ability of blood cells and their microparticles to transport monomeric and pentameric forms of C-reactive protein (mCRP and pCRP) in the blood of patients with coronary artery disease (CAD). Blood was obtained from 14 patients with CAD 46 ± 13 years old and 8 healthy volunteers 49 ± 13.6 years old. Blood cells and microparticles with mCRP and pCRP on their surface were detected by flow cytometry. Messenger RNA (mRNA) of CRP was extracted from peripheral blood monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…[28][29] Moreover, it was reported that monocytes can transport CRP in blood ow through monocyte-derived exosomes to maintain chronic in ammation. 30 The ndings of the current study presented signi cant negative correlation between MDW and total platelet (r=-0.140, p < 0.05).…”
Section: Discussionmentioning
confidence: 44%
“…[28][29] Moreover, it was reported that monocytes can transport CRP in blood ow through monocyte-derived exosomes to maintain chronic in ammation. 30 The ndings of the current study presented signi cant negative correlation between MDW and total platelet (r=-0.140, p < 0.05).…”
Section: Discussionmentioning
confidence: 44%
“…Plasma levels of the leukocyte-derived EVs were elevated in patients with hypertension and hyperlipidemia [ 51 ]. Melnikov et al [ 52 ] identified monocytes-derived EVs carrying monomeric C-reactive protein (mCRP) in the blood that was associated with inflammatory status in CAD patients.…”
Section: Origins Of Extracellular Vesicles Related To Cvdmentioning
confidence: 99%
“…Serum EV proteins, such as cystatin C, polygenic immunoglobulin receptor (pIgR) and complement factor C5a (C5a), were suggested to be associated with ACS [ 117 , 140 ]. mCRP carried by monocyte-derived EVs was associated with inflammatory process in patients with CAD [ 52 ]. EVs can transport and delivery pro-inflammatory mCRP in endothelial cells [ 118 ].…”
Section: Extracellular Vesicle As Biomarkers In Cvdmentioning
confidence: 99%
“…An unbound fraction of mCRP has also recently been reported in serum of patients with high levels of circulating native CRP (>100 mg/L, in the range of acute inflammatory response), although the dissociation site of origin is unclear [19]. Furthermore, mCRP has been detected in U937-derived macrophages [20] and exosomes derived from monocytes of patients with coronary artery disease [21]. Additionally, other cell types such as neurons in the AD brain may produce CRP, albeit in lower amounts than hepatocytes [22].…”
Section: Introductionmentioning
confidence: 95%